The Impact of Tourism on Electricity Imports by Thailand from Lao People's Democratic Republic - Nonthapot, Sakkarin (International Journal of Energy Economics and Policy, 2020)
The objective of this research is to explain how Thai tourism affects the quantity of electricity imported by Thailand from Lao PDR. Data were quarterly data from 2000 to 2019 estimated with the autoregressive distributed lag (ARDL) procedure. The results show that all variables are cointegrated. For the long-run equilibrium, tourism and income factors have a positive effect on the quantity of electricity imports. In the short-run equilibrium, income, price, exchange rate and tourism factors will return to long-term equilibrium by approximately 16 percent in each time period. From the study results, the international tourism demand expansion of Thailand needs to supported by electricity imports from Lao PDR. Therefore, Thailand should focus on forecasting the number of international tourists coming to Thailand, which will allow an efficient use of the electricity reserves of Thailand in order to provide a sustainable supply of electrical energy. Keywords: Electricity import; Tourism; International Tourism JEL Classifications: F1; Z3; Q4 DOI: https://doi.org/10.32479/ijeep.9991